Reductive cyclotetramerization of CO to squarate by a U(III) complex: the X-ray crystal structure of [(U (eta-C8H6{SiiPr3-1,4}2)(eta-C5Me4H)]2(mu-eta2: eta2-C4O4). - Summerscales, O; Cloke, F; Hitchcock, P; Green, J; Hazari, N (2006)
The U(III) mixed-sandwich compound [U(eta-C5Me4H)(eta-C8H6{SiiPr3-1,4}2)(THF)] 1 may be prepared by sequential reaction of UI3 with K[C5Me4H] in THF followed by K2[C8H6{SiiPr3-1,4}2]. 1 reacts with carbon monoxide at -30 degrees C and 1 bar pressure in toluene solution to afford the crystallographically characterized dimer [(U(eta-C8H6{SiiPr3-1,4}2)(eta-C5Me4H)]2(mu-eta2: eta2-C4O4) 2, which contains a bridging squarate unit derived from reductive cyclotetramerization of CO. DFT computational studies indicate that addition of a 4th molecule of CO to the model deltate complex [U(eta-COT)(eta-Cp)]2(mu-eta1: eta2-C3O3)] to form the squarate complex [U(eta-COT)(eta-Cp)]2(mu-eta2: eta2-C4O4)] is exothermic by 136 kJ mol-1.